Phytochemical Screening And Identification of Terpenoids Compounds at Ethanolic Extract Pegagan Leaves (Centella asiatica L. Urban) - Astari, Weni (JBIO: jurnal biosains (the journal of biosciences), 2024)
Terpenoids are one of the secondary metabolite compounds that have animportant role in medicine because they have many benefits in healingvarious diseases. Terpenoids are also believed to be contained in gotu kolaleaves. This research was conducted to find out what are the activecompounds contained in gotu kola leaves. This research begins withextracting 400 grams of gotu kola leaf powder with 96% ethanol solventusing the maceration method. The results of maceration were thenevaporated using a waterbath until a thick extract was obtained.Identification of active compounds contained in gotu kola leaves wascarried out by phytochemical screening test and KLT test on thick extract.In the phytochemical screening test, it is known that the ethanol extract ofgotu kola leaves positively contains terpenoids, steroids and saponins.Then the identification of compounds using the KLT method withethanol:ethyl acetate eluent in a ratio of 9:1, 8:2, 7:3 and 6:4, then sprayedwith reagent liquid and observed under a UV lamp with a wavelength of254 nm. In the ratio of 9:1, the resulting Rf value is 0.64. Then in the ratioof 8:2 and 7:3, the resulting Rf values were 0.67 and 0.69. And in the ratioof 6:4, the resulting Rf value is 0.75. Based on the Rf value obtained, itcan be concluded that the ethanol extract of gotu kola leaves can certainlycontain terpenoid derivative compounds, namely triterpenoids which havea standard Rf value of 0,50-0,89